2019
DOI: 10.1101/699355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MicroRNA-378 suppressed osteogenesis of mesenchymal stem cells and impaired bone formation via inactivating Wnt/β-catenin signaling

Abstract: 37MicroRNAs (miRNAs) have been reported to serve as silencers to repress gene 38 expression at post-transcriptional level. Multiple miRNAs have been demonstrated to 39 play important roles in osteogenesis. MiR-378, a conserved miRNA, was reported to 40 mediate bone metabolism and influence bone development, but the detailed function 41 and underlying mechanism remain obscure. In this study, the miR-378 transgenic (TG) 42 mouse was developed to study the role of miR-378 in osteogenic differentiation as 43… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Transfection of microRNA-127 inhibitor enhances osteogenesis in UAM-32 cells as measured by ALP activity and mRNA expression of RUNX2, and transfection of microRNA-136 precursor has inhibitory effects on osteoblastic differentiation, indicating that both microRNA-127 and microRNA-136 negatively regulate osteoblast differentiation [91]. Feng et al found abnormal bone tissues and impaired bone quality in microRNA-378 transgenic mice [92]. It was observed that microRNA-378 suppresses osteogenesis of hBMSCs by targeting Wnt10 and eventually induces the inactivation of Wnt/β-catenin signalling.…”
Section: Micrornas Involved In Bone/fat Formationmentioning
confidence: 99%
“…Transfection of microRNA-127 inhibitor enhances osteogenesis in UAM-32 cells as measured by ALP activity and mRNA expression of RUNX2, and transfection of microRNA-136 precursor has inhibitory effects on osteoblastic differentiation, indicating that both microRNA-127 and microRNA-136 negatively regulate osteoblast differentiation [91]. Feng et al found abnormal bone tissues and impaired bone quality in microRNA-378 transgenic mice [92]. It was observed that microRNA-378 suppresses osteogenesis of hBMSCs by targeting Wnt10 and eventually induces the inactivation of Wnt/β-catenin signalling.…”
Section: Micrornas Involved In Bone/fat Formationmentioning
confidence: 99%